Synthesis, structural, optical and electrical properties of metal nanoparticle-rare earth ion dispersed in polymer film - Kumar B.; Kaur G.; Singh P.; Rai S.B. (My University, 2025)
Cu-nanoparticles have been prepared by ablating a copper target submerged in benzene with laser pulses of Nd:YAG (wavelength: 355, 532 nm and 1,064 nm). Colloidal nanoparticles have been characterized by UV-Vis spectroscopy and transmission electron microscopy. The obtained radius for the nanoparticles prepared using 1,064 nm irradiation lies in the range 15-30 nm, with absorption peak at 572 nm. Luminescence properties of Tb3+ ions in the presence and absence of Cu-nanoparticles have been investigated using 355 nm excitation. An enhancement in luminescence of Tb3+ by local field effect causing increase in lifetime of 5D4 level of Tb3+ ion has been observed. Frequency and temperature-dependent conductivity of Tb3 + doped PVA thin films with and without Cu-nanoparticles have been measured in the frequency range 20 Hz-1 MHz and in the temperature range 318-338 K (well below its melting temperature). Real part of the conductivity spectra has been explained in terms of power law. The electrical properties of the thin films show a decrease in dc conductivity on incorporation of the Cu-nanoparticles. © 2013 Springer-Verlag Berlin Heidelberg.